ANTIBACTERIAL THERAPY OF SEPTIC COMPLICATIONS IN RESISTANCE OF PATHOGENS TO CARBAPENEMS - T. V. Chernenkaya (Neotložnaâ Medicinskaâ Pomoŝʹ, 2017)
Today, the resistance of Gram-negative bacteria to carbapenems becomes a global problem. Standard regimens of antibiotic treatments are noted to be ineffective in the development of diseases, caused by such pathogens, which resulted in a significant increase in hospital stay duration, cost of treatment and mortality rate. The review of literature describes therapeutic opportunities for treatment of diseases caused by pathogens resistant to carbapenems.